A Review of Solar Thermochemical CO2 Splitting Using Ceria-Based Ceramics With Designed Morphologies and Microstructures - Pullar, Robert C.; Novais, Rui M.; Caetano, Ana P. F.; Barreiros, Maria Alexandra; Abanades, Stéphane; Oliveira, Fernando A. Costa (Frontiers in Chemistry, 2019)
This review explores the advances in the synthesis of ceria materials with specific morphologies or porous macro- and microstructures for the solar-driven production of carbon monoxide (CO) from carbon dioxide (CO2). As the demand for renewable energy and fuels continues to grow, there is a great deal of interest in solar thermochemical fuel production (STFP), with the use of concentrated solar light to power the splitting of carbon dioxide. This can be achieved in a two-step cycle, involving the reduction of CeO2 at high temperatures, followed by oxidation at lower temperatures with CO2, splitting it to produce CO, powered by concentrated solar power (CSP) to provide the high reaction temperatures of typically up to 1500 ºC. Since cerium oxide was first explored as a solar-driven redox catalyst in 2006, and to specifically split CO2 in 2010, there has been an increasing interest in this material. The solar-to-fuel conversion efficiency is influenced by the material composition itself, but also by the material morphology that mostly determines the available surface area for solid/gas reactions (the material oxidation mechanism is mainly governed by surface reaction). The diffusion length and specific surface area affect, respectively, the reduction and oxidation steps. They both depend on the reactive material morphology that also substantially affects the reaction kinetics and heat and mass transport in the material. Accordingly, the main relevant options for materials shaping are summarised. We explore the effects of microstructure and porosity, and the exploitation of designed structures such as fibres, 3-DOM (three-dimensionally ordered macroporous) materials, reticulated and replicated foams, and the new area of biomimetic/biomorphous porous ceria catalysts produced from natural and sustainable templates such as wood or cork, sometimes known as ecoceramics.